2016
DOI: 10.1103/physreva.93.063636
|View full text |Cite
|
Sign up to set email alerts
|

Second-order virial expansion for an atomic gas in a harmonic waveguide

Abstract: The virial expansion for cold two-component Fermi and Bose atomic gases is considered in the presence of a waveguide and in the vicinity of a Feshbach resonance. The interaction between atoms and the coupling with the Feshbach molecules is modeled using a quantitative separable two-channel model. The scattering phase-shift in an atomic waveguide is defined. This permits us to extend the Beth-Uhlenbeck formula for the second-order virial coefficient to this inhomogeneous case.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Beth and Uhlenbeck, in their famous paper [2], showed that this shift δb 2 is related to the scattering phase shift in 3D. Since then the result has been generalized in lower dimensions as well [3][4][5]. Recently, it was proven that δb 2 is the imprint of the quantum scale anomaly in dilute quantum gases in 1D with three-body and 2D with two-body local interactions [6,7] using a many-body path integral formalism [8].…”
Section: Introductionmentioning
confidence: 98%
“…Beth and Uhlenbeck, in their famous paper [2], showed that this shift δb 2 is related to the scattering phase shift in 3D. Since then the result has been generalized in lower dimensions as well [3][4][5]. Recently, it was proven that δb 2 is the imprint of the quantum scale anomaly in dilute quantum gases in 1D with three-body and 2D with two-body local interactions [6,7] using a many-body path integral formalism [8].…”
Section: Introductionmentioning
confidence: 98%